BRONZE NOSE RINGS FROM THE BURIAL OF THE EARLY BRONZE AGE IN THE NORTH CAUCASUS - Denaeva, Alla Sergeevna; Zajcev, Il'a Aleksandrovic; Il'ukov, Leonid Sergeevic (History, Archeology and Ethnography of the Caucasus, 2021)
In 2017, in a single burial mound in the Novosrednenskoye-1 burial ground, located near the village of the same name in the Kirovsky district of the Stavropol Territory, a burial was examined on an ancient horizon, over which an earthen embankment was erected. The deceased was in a wooden box, on the ceiling of which were the skulls of two bulls with bronze nose rings. A small series of burial complexes found in burials on the territory of the North Caucasus, in which nose rings were found, are considered. They were used to control animals harnessed to a cart. A symbolic team of two bulls was used to travel the soul of the deceased into the world of their ancestors. In the Novosvobodnenskoe time, a fashion emerged for the use of wire oval pendants, which were fixed not in the puncture of the nasal septum, but in the punctures of the earlobes. Such pendants, made of bronze or silver wire, were popular in the Novotitarovskaya culture, which replaced the Novosvobodnaya culture.